2018
DOI: 10.1053/j.gastro.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hepatocellular Cancer in Patients With Non-Alcoholic Fatty Liver Disease

Abstract: Risk of HCC was higher in NAFLD patients than that observed in general clinical population. Most HCC cases in NAFLD developed in patients with cirrhosis. The absolute risk of HCC was higher than the accepted thresholds for HCC surveillance for most patients with NAFLD cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
510
1
25

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 589 publications
(607 citation statements)
references
References 25 publications
18
510
1
25
Order By: Relevance
“…Furthermore, NAFLD was classified as an underlying etiology of HCC purely based on risk factors (diabetes and obesity in the absence of other evidence of CLD), which raises concern for misclassification. Another recent VA study showed that diabetes is associated with a 3‐fold increased risk of HCC in NAFLD patients after adjusting for covariates . In the cirrhosis subgroup, a higher incidence rate of HCC was observed in patients with diabetes (12.4 in diabetics vs. 8.5 in nondiabetics per 1,000 person‐years) .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Furthermore, NAFLD was classified as an underlying etiology of HCC purely based on risk factors (diabetes and obesity in the absence of other evidence of CLD), which raises concern for misclassification. Another recent VA study showed that diabetes is associated with a 3‐fold increased risk of HCC in NAFLD patients after adjusting for covariates . In the cirrhosis subgroup, a higher incidence rate of HCC was observed in patients with diabetes (12.4 in diabetics vs. 8.5 in nondiabetics per 1,000 person‐years) .…”
Section: Discussionmentioning
confidence: 97%
“…Another recent VA study showed that diabetes is associated with a 3‐fold increased risk of HCC in NAFLD patients after adjusting for covariates . In the cirrhosis subgroup, a higher incidence rate of HCC was observed in patients with diabetes (12.4 in diabetics vs. 8.5 in nondiabetics per 1,000 person‐years) . Multivariate analysis was not performed in the cirrhosis subgroup; thus, an adjusted HR was not reported .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Increasing secular trends in incidence and mortality have been observed across many countries including the United Kingdom, Poland, Brazil, Germany and Norway . Major risk factors for liver cancer include hepatitis C virus (HCV) infection, hepatitis B virus (HBV) infection, heavy alcohol drinking and nonalcoholic fatty liver disease (NAFLD) . With further increases in liver cancer incidence predicted, there is growing interest in identifying modifiable risk factors for liver cancer, especially those that can be targeted with medications, such as aspirin and nonsteroidal antiinflammatory drugs (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%